Effect of Feed Supplement and Probiotics on Growth Performance of Japanese Quails - Gupta, N.K.; Shrivastava, A.K.; Praveen, P.K.; Ganguly, S. (Indian Journal of Animal Nutrition, 2018)
The study was conducted on 120 day-old Japanese quail chicks under deep litter system which were randomly divided into four group viz., T1, T2, T3 and T4 of thirty birds each. Group T1, T2 and T3 were given feed supplement, probiotic and their combination, respectively along with basal diet and the group T4 was kept as control. At 6 week age, higher (P<0.05) body weight was observed in group T3 (147.33±2.57 g) and T1 (147.00±4.58 g) in comparison to group T2 (127.00±4.24 g) and T4 (125.27±4.28). The average FCR was better in group T3 (3.24±0.44) followed by T1 (3.26±0.45), T2 (3.68±0.58) and T4 (3.81±0.60) during 0-6 weeks age. The present finding suggested that the feed supplement, probiotic and their combination might be utilized in Japanese quail farming under deep litter system.